Characteristics and Role of Women at Small Industries Manufacturing Leading in Sumedang-Indonesia and gender inequality are felt - Zuraida, Umi; ., Sri Herliana; ., Sri Hartati (Journal of Social and Development Sciences, 2014)
The purpose of this study is to know the characteristics, role and gender inequality that was received in a workplace and in the home by women who work at small industries manufacturing leading in Sumedang district. Result of study can be used as a reference in realizing the government’s policy of increasing role of women’s doubles at the small industries. The research use descriptive analysis. Sample is 60 women who work at 15 main small industries that were taken by purposive. Primary data with questionnaire accompanied by interviews and direct observation. Women who engaged in small industries in manufacturing commodity Sumedang district have characteristic: all within the productive age with the highest number (76%) between 16 -30 years. Majority (60%) from primary school and 90% earn below the minimum wages. 50% of respondents turn over all the proceeds to the family, because motivation of their work is 53% to help their husbands in order to improve economy of family. Contribution to the family economy is 60% contribute very small, because their contribution just becomes part of the contribution of all other family members. Their role is majority (60 %) at finishing and packing. The respondent feel there is gender equality at the workplace, but there is still inequality in the family even though they not feel that it is an inequality.